KAJIAN TERHADAP VALIDASI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SEBAGAI SYARAT PERALIHAN HAK ATAS TANAH DI KABUPATEN SUKOHARJO - Andria Luhur Prakoso; Muhammad Annam Arroffi Tixatmojo (Universitas Muhammadiyah Ponorogo, 2023)
Tax is the biggest income for the state treasury. One of the largest tax objects whose largest income is BPHTB. The acquisition fee for land and building rights is a tax that is imposed on the transfer of land and building rights, hereinafter referred to as tax. The Land and Building Title Transfer Fee is a tax whose authority and management is owned by the Central Government, but with the implementation of regional autonomy, the authority of BPHTB is assigned to the Regional Government. This study will examine the process of BPHTB in Sukoharjo Regency, especially the validation which is one of the processes of BPHTB. The problem formulations in this journal are: 1. The urgency of BPHTB validation in the transfer of land rights; and 2. The barriers to BPHTB validation. The aims of this study are to find out the validation process of BPHTB in the transfer of land rights, to ascertain how important is BPHTB validation in the transfer of land rights, and to identify the obstacles in the BPHTB validation process. The research method used is legal research with a normative type of research using a legal approach and a conceptual approach. The finding of this study is that the BPHTB validation process is an important process because it acts as a precaution for checking after the tax payment process, this is due to the requirement that the tax payment procedure be correctly completed in compliance with applicable regulations. There are still challenges in this tax validation to be solved.